Le passif peut-il éclairer les esprits ? - Valentina Vapnarsky (Ateliers d'Anthropologie)
This article presents an examination of modes of expressing and attributing agency in verbal interactions concerning master-spirits among the Yucatec Maya of Quintana Roo (Mexico). The study combines a grammatical analysis of how notions pertaining to agency structure the Yucatec Maya, with an ethnographic and discursive analysis of interactions involving spirits. Four discursive situations are compared: personal accounts of encounters with spirits, stories, comments from the ritual specialist, ritual invocation. These reveal sharp contrasts with regard to the grammatical and lexical modes of reference used to refer to spirits, making it possible, through a consideration of types of relatively typified discourse and local discursive choices, to detail certain correlations between participatory framework, linguistic mode of reference and relational system. The hypothesis put forward is that linguistic modes of reference to spirits and to their actions are jointly constitutive of the forms and gradations of agency that are assigned to them, insofar as they index, qualify or obliterate typified and contextual relationships of agency between the speaker, other participants in the speech event, and spirits.